Infrared and Laser Raman Spectral Studies of 2-Cyanopyridine - Isaq, M.; Gupta, S.P.; Sharma, S.D.; Ahmad, S. (Asian Journal of Chemistry, 2010)
The infrared absorption (4000–200 cm-1) and laser RamanSpectra (3500-100 cm-1) of 2-cyanopyridine are reported. Anassignment of fundamentals is proposed and its comparison withsimilar molecule is included.